Γ‐Fe2O3@Cu3Al‐LDH‐TUD as a new Amphoteric, Highly Efficient and Recyclable Heterogeneous Catalyst for the Solvent‐free Synthesis of Dihydropyrano[3, 2‐c]pyrazoles and dihydropyrano[3, 2‐c]chromens. (22nd February 2018) - Azarifar, Davood; Tadayoni, Mehrdad; Ghaemi, Masoumeh
Abstract : Thiourea dioxide was immobilized on γ‐Fe2 O3 @Cu3 Al‐LDH magnetic nanoparticles to prepare the γ‐Fe2 O3 @Cu3 Al‐LDH‐TUD MNPs. The structure and properties of these magnetic nanoparticles were established by FT‐IR, EDX, SEM, XRD, and hystogram of particle size analytical methods. The results obtained from these analytical methods confirmed the successful immobilization of the thiourea dioxide onto the magnetic support. The synthesized magnetic nanoparticles (MNPs) exhibited high catalytic activity in one‐pot three‐component reactions under mild and solvent‐free conditions for the synthesis of diverse ranges of dihydropyrano[3, 2‐ c ]pyrazoles and dihydropyrano[3, 2‐ c ]chromens. All the reactions proceeded smoothly to furnish the respective products in excellent yields. Simple isolation of the products, avoidance of harmful organic solvents, versatility of the catalyst and its easy magnetic separation and reusability with no significant loss of activity are the main advantages of the present method. Abstract : Application of new amphoteric nanocatalyst (γ‐Fe2 O3 @Cu3 Al‐LDH‐TUD) for the synthesis of Dihydropyrano[2, 3‐c]pyrazoles and dihydropyrano[3, 2‐c]chromens under sovent free condition.